SARS-CoV-2 Origin and COVID-19 Pandemic Across the Globe - Kumar, Vijay (IntechOpen, 2021)
The current COVID-19 pandemic has infected more than 219 million people and killed more than 4.5 million people worldwide. It has also impacted the socioeconomic status of affected countries and led to the fastest development of vaccines in history. Over seven sections and seventeen chapters, this book comprehensively reviews numerous aspects of COVID-19, including epidemiology, zoonosis, drug development, telehealth, the effects of the virus on healthcare workers, the importance of architecture, and urbanism in preventing future pandemics, and much more.